DETERMINAN KUALITAS PELAPORAN KEUANGAN DAN KONSEKUENSI EKONOMINYA DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL INTERVENING - Riyanto Setiawan Suharsono; Achmad Syahfrudin Zulkarnnaeni; Ayu Widia Lestari; Pratiwi Dwi Libriana (Universitas Muhammadiyah Jember, 2023)
This study aims to examine the determinants of financial reporting quality and its economic consequences with Good Corporate Governance (GCG) as an intervening variable. This research is a quantitative study that analyzes the relationship between determinants of financial reporting quality and its economic consequences with GCG as an intervening variable. The sample in this research is 108 manufacturing companies listed on the Indonesia Stock Exchange from 2017 to 2021. The sampling technique uses a purposive sampling technique. The data analysis technique used in this study is path analysis. The results of the study show that there is a direct influence of the Determinant Factors and GCG on the quality of financial reporting. The results also show that there is a direct effect of GCG on information asymmetry. The results also show that there is an indirect influence of the Determinant Factor on the quality of financial reporting through information asymmetry. The indirect effect of GCG on the quality of financial reporting through information asymmetry was not found in this study.